1994
DOI: 10.1111/j.1539-6924.1994.tb00025.x
|View full text |Cite
|
Sign up to set email alerts
|

A Distributional Approach to Characterizing Low‐Dose Cancer Risk

Abstract: Since cancer risk at very low doses cannot be directly measured in humans or animals, mathematical extrapolation models and scientific judgment are required. This article demonstrates a probabilistic approach to carcinogen risk assessment that employs probability trees, subjective probabilities, and standard bootstrapping procedures. The probabilistic approach is applied to the carcinogenic risk of formaldehyde in environmental and occupational settings. Sensitivity analyses illustrate conditional estimates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 17 publications
0
25
0
Order By: Relevance
“…Evans et al (53,54) developed and demonstrated such methods in the context of health experts' judgments about low-dose cancer risk from exposure to formaldehyde in environmental and occupational settings. The method used the construction of probability trees that allowed experts to make judgments about the relative likelihood that alternative models of possible pharmacokinetic and pharmacodynamic processes correctly describe the biological process that are involved.…”
Section: Uncertainty About Model Functional Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Evans et al (53,54) developed and demonstrated such methods in the context of health experts' judgments about low-dose cancer risk from exposure to formaldehyde in environmental and occupational settings. The method used the construction of probability trees that allowed experts to make judgments about the relative likelihood that alternative models of possible pharmacokinetic and pharmacodynamic processes correctly describe the biological process that are involved.…”
Section: Uncertainty About Model Functional Formmentioning
confidence: 99%
“…The process they developed is very labor intensive and uses experts as evaluators of alternative causal models and their implications rather than as proponents of one or another model. It would be highly desirable to apply procedures such as those developed and demonstrated by Evans et al (53,54) and Budnitz et al (55,56) in assessment processes such as that used by the Intergovernmental Panel on Climate Change (IPCC). However, resource constraints and the limited familiarity that most experts have with decision science, probably makes such an effort infeasible.…”
Section: Uncertainty About Model Functional Formmentioning
confidence: 99%
“…Most analysts in the field of environmental risk analysis would agree, however, that uncertainty in doseresponse relationships often overwhelms any uncertainty from other sources including exposure ( Taylor et al, 1993, Thompson andEvans, 1997 ). Other studies have suggested that uncertainty in dose response may span orders of magnitude ( Evans et al, 1994 ).…”
Section: Introductionmentioning
confidence: 99%
“…These are not simple questions and the choice made can be significant. As a simple demonstration, using analysis from Evans et al (1994) and assuming 10,000.0000 people exposed to a background level of 3.45 ppb of formaldehyde in air, 20 m3 air breathed per day and 70 years of exposure the choice of dose-response model leads to prediction of excess cancers of 0 for a probit model, <1 for a multistage model, and about 21,000 for a one-hit model. In the absence of compelling information about the scientific appropriateness of one model or another, the choice becomes a matter of science policy.…”
Section: Science Policymentioning
confidence: 99%